From policy to practice: Evaluating the implementation of intercultural competence in vocational english classrooms in China - Liang Yinyin; Abdul Said Ambotang (Human Resource Management Academic Research Society, 2025)
As China’s vocational education system becomes increasingly international, integrating intercultural communication competence (ICC) into English education has become a national priority. Policy documents such as China's Education Modernization 2035 and the English Curriculum Standards for Higher Vocational Education Institutions (2021) emphasize the cultivation of ICC to enhance global employability. However, questions remain about how these policy directives will be interpreted and implemented in the classroom. This study investigates the implementation of ICC in specialist English classrooms through classroom observations, semi-structured interviews with teachers and students, and analysis of teaching materials documents. The study uses the Integrated Model of Intercultural Communicative Competence (IMICC) to identify how ICC is reflected in teaching practices, teachers’ understanding, and students’ experiences. The results show significant differences in the integration of ICC across institutions, including limited teacher training, superficial coverage of intercultural topics, and a focus on language over intercultural goals. The article concludes with contextual recommendations for improving ICC teaching and better aligning teaching practices with national policy goals.